2019
DOI: 10.22159/ajpcr.2019.v12i7.33771
|View full text |Cite
|
Sign up to set email alerts
|

Helichrysum Cymosum (L.) D.DON (Asteraceae): Medicinal Uses, Chemistry, and Biological Activities

Abstract: Helichrysum cymosum is a valuable and well-known medicinal plant in tropical Africa. The current study critically reviewed the medicinal uses, phytochemistry and biological activities of H. cymosum. Information on medicinal uses, phytochemistry and biological activities of H. cymosum, was collected from multiple internet sources which included Scopus, Google Scholar, Elsevier, Science Direct, Web of Science, PubMed, SciFinder, and BMC. Additional information was gathered from pre-electronic sources such as jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Francois (2016) investigated the anti-oxidant capacity of the essential oils isolated from H. cymosum leaves using the 1, 1 diphenyl 1-picrylhydrazyl (DPPH) assay. Results obtained showed that 50% free radical scavenging activity was achieved by the 6.3 g/L concentration of this plant compared to the same effects by the 7.0 mg/L concentration of the positive control, butylated hydroxytoluene (BHT), a known compound used as a food anti-oxidant additive [29]. Thus, the extract of this plant had more anti-oxidant effects than BHT, indicating potential use as food additives.…”
Section: Anti-oxidant Activity Of H Cymosummentioning
confidence: 95%
See 2 more Smart Citations
“…Francois (2016) investigated the anti-oxidant capacity of the essential oils isolated from H. cymosum leaves using the 1, 1 diphenyl 1-picrylhydrazyl (DPPH) assay. Results obtained showed that 50% free radical scavenging activity was achieved by the 6.3 g/L concentration of this plant compared to the same effects by the 7.0 mg/L concentration of the positive control, butylated hydroxytoluene (BHT), a known compound used as a food anti-oxidant additive [29]. Thus, the extract of this plant had more anti-oxidant effects than BHT, indicating potential use as food additives.…”
Section: Anti-oxidant Activity Of H Cymosummentioning
confidence: 95%
“…cymosum and H. cymosum subsp. calvum Hilliard [28,29], with distinct characteristics in the flowers, fimbrils, ovary, pappus, and plant length [29]. Traditionally, the aerial parts, leaves, roots, and leaves of this plant are used to treat different ailments ranging from cough, catarrh, colds, headache, menstrual pain, fever, wounds, flatulence, pulmonary problems, skin infections, pertussis vomiting as well as to improve immunity, and appetite [15,29].…”
Section: Helichrysum Cymosum and Its Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Helichrysum cymosum (Figure 1A) is traditionally used to treat colds, coughs, fever, headaches, and wounds [17,18]. Other ethnomedicinal uses of H. cymosum include pertussis, influenza, treatment of blocked nose, pulmonary problems, flatulence, diarrhea, improve appetite, laxative, vomiting, dizziness, insomnia, boosting the immune system, skin infections, varicose veins, weak bones, menstrual pain, insect repellent, cardiovascular problems, kidney problems, urinary problems, and eye problems [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other ethnomedicinal uses of H. cymosum include pertussis, influenza, treatment of blocked nose, pulmonary problems, flatulence, diarrhea, improve appetite, laxative, vomiting, dizziness, insomnia, boosting the immune system, skin infections, varicose veins, weak bones, menstrual pain, insect repellent, cardiovascular problems, kidney problems, urinary problems, and eye problems [17]. The leaves, stems, and twigs of H. cymosum are sold as herbal medicines in the informal herbal medicine markets in the Gauteng and the Western Cape provinces in South Africa [18]. Numerous compounds have been isolated from the alcoholic extract of the leaves and roots of H. cymosum including different sesquiterpenes and chalcones [19][20][21].…”
Section: Introductionmentioning
confidence: 99%